Alat Pemantau Detak Jantung dan Pernafasan dengan Sistem Mikrokontroler - Abdulmanan Maliki; Jana Utama (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2018)
Abstract - The heart is a vital organ in the body whose role is very important in the survival of someone other than the brain, because the heart is responsible for circulating blood throughout the body. And the blood carries oxygen in hemoglobin to meet the oxygen needs in the body. The oxygen demand in the body can be fulfilled through the process of respiration. Oxygen is needed by every cell in the human body. in the process of biochemical reactions (biological oxidation) that function produces ATP (Adenosin Tri Phosphat) energy. The results of substances that occur in the form of residual carbon dioxide and water vapor then exhaled. So the breathing process is needed by humans to get ATP which is useful for doing various activities. Heart rate and respiration measurements can provide important information about the condition or work system of vital organs such as the heart and lungs. Although there are several ways to measure heart rate and respiration rate, the most efficient method of measurement is needed without having to involve manual measurements that can interfere with patient comfort. The Photoplethysmography (PPG) technique is one method of measuring heart rate that can be applied because it is non-invasive so it does not interfere with patient comfort while monitoring heart rate. Whereas to measure the level of respiration can be done by using a temperature sensor that is placed on the air outlet, namely in the mouth. This project aims to create a stand-alone pulse rate and respiration monitoring device that monitors the data can be seen via LCD.Keyword : heart, respiration, photoplethysmography, adenosina trifosfat, oxygen